2023
DOI: 10.1037/fam0001098
|View full text |Cite
|
Sign up to set email alerts
|

The spread of political alienation from parents to adolescent children.

Abstract: The present study examines the interpersonal circumstances that facilitate the spread of political alienation between parents and adolescent children. A total of 571 German adolescents (314 girls, 257 boys) and their mothers and fathers each completed questionnaires describing their own political alienation at two time points, approximately 1 year apart. In addition, adolescents completed questionnaires describing their perceptions of warmth in relationships with parents. Adolescents were in the sixth (M = 12.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Of the many factors that shape young people's political development, experiences in proximal contexts, such as home, school, or the peer group, have gained particular attention (Neundorf and Smets, 2017). Research has shown that young people encounter politics at school (Miklikowska et al, 2019;Noack and Eckstein, 2023) and adopt political attitudes from parents (Miklikowska, 2016;Legget-James et al, 2023) or other family members (Eckstein et al, 2018). Yet, in line with contextual models of human development (Bronfenbrenner, 1979), more distal macro-contexts such as societal events (e.g., wars, political upheavals, scandals) also play a role.…”
Section: Introductionmentioning
confidence: 99%
“…Of the many factors that shape young people's political development, experiences in proximal contexts, such as home, school, or the peer group, have gained particular attention (Neundorf and Smets, 2017). Research has shown that young people encounter politics at school (Miklikowska et al, 2019;Noack and Eckstein, 2023) and adopt political attitudes from parents (Miklikowska, 2016;Legget-James et al, 2023) or other family members (Eckstein et al, 2018). Yet, in line with contextual models of human development (Bronfenbrenner, 1979), more distal macro-contexts such as societal events (e.g., wars, political upheavals, scandals) also play a role.…”
Section: Introductionmentioning
confidence: 99%